How do the leadership styles impact the performance of professional competences in Brazilian workers? Identifying mechanisms and contextual variables. - Couto, Fernando José Barbato; Coelho Junior, Francisco Antonio; Santos, Andersson Pereira dos; Marques-Quinteiro, Pedro; Faiad, Cristiane (Open Science Journal, 2022)
The study of the influence of the leadership styles on the behavior of the followers is of great relevance. Leadership is an important function of management which helps to maximize efficiency and to achieve organizational goals. Usually, the performance of followers is influenced by the performance of the leader and his or her behavior acting a job. The aim of this paper is to provide empirical evidence on the impact exerted by the leadership style, if oriented by tasks or oriented by relationship/people, on the performance of 168 Brazilian leaders. Two validated and structured questionnaires were applied. All recommended ethical procedures were adopted. Using multiple linear regression, we confirmed that leadership styles influences individual performance. Depending on the way in which the team is characterized, the leadership styles will be less or more influential. In the context of heterogeneous teams, the influence of leaders tends to be predominantly task-based. A limitation of this research was the sample size. The findings have important implications for the organizational studies, leaders and organizations.